2020
DOI: 10.5539/ass.v16n10p69
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effect of Idealized Influence Between Relationship Emotional Intelligence and Intention to Perform: Conceptual Study

Abstract: Academics have an enormous endeavor to advance in higher education institutions, and responsiveness regarding to their performance, leaders’ emotional intelligence and leaders’ idealized influence are fundamental. Research on emotional intelligence and job performance is expanding at considerable pace, but emotional intelligence and intention to perform has received less attention. In addition, study on transformational leadership towards intention to perform has been established but study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 89 publications
(110 reference statements)
0
0
0
Order By: Relevance
“…On the contrary, some of the leaders used less of symbols and emotional appeals to align their followers. These results are in line with a previous study by Raman et al (2020) that showed that the aspects of setting a clear vision, articulating effective objectives, and stimulating employees improved their performance.…”
Section: Table 2: Inspirational Motivationsupporting
confidence: 92%
“…On the contrary, some of the leaders used less of symbols and emotional appeals to align their followers. These results are in line with a previous study by Raman et al (2020) that showed that the aspects of setting a clear vision, articulating effective objectives, and stimulating employees improved their performance.…”
Section: Table 2: Inspirational Motivationsupporting
confidence: 92%